Efavirenz Outperforms Boosted Atazanavir among Treatment-Naive HIV-1-Infected Persons in Routine Clinical Care. (March 2013) - Taniguchi, Toshibumi; Grubb, Jessica R.; Nurutdinova, Diana; Önen, Nur F.; Shacham, Enbal; Donovan, Michael; Overton, Edgar Turner
Background: Effectiveness of antiretroviral therapy (ART) in a routine clinical care may result different from the clinical trials. We assessed the virologic outcomes in treatment-naive persons who received either efavirenz (EFV) or atazanavir/ritonavir (ATV/r) with a backbone of tenofovir/emtricitabine (TDF/FTC) as their combination ART (cART). Methods: This was a retrospective cohort study conducted at the Washington University HIV Outpatient Clinic from January 2004 to June 2009.  Predictors of virologic suppression (HIV RNA level <400 copies/mL) by week 48 were assessed by multivariate Cox proportional hazards regression models. Results: Of 324 persons, 221(68%) received EFV and 103 (32%) received ATV/r. Persons on EFV had 1.4-fold increased likelihood of virologic suppression (95% confidence interval, 1.0-1.8) when compared to ATV/r after adjustment with primary drug resistance, pre-cART opportunistic infection, HIV RNA levels, and timing to start cART. Conclusions: In routine clinical care settings, EFV had higher likelihood of achieving virologic suppression than ATV/r with backbone of TDF/FTC.